Peranan budaya dan kepercayaan makan singkong masyarakat adat Cireundeu dalam menjaga kelestarian alam: Studi literatur - Nisa, Hana Khoirun; Surtikanti, Hertien Koosbandiah (Journal of Socio-Cultural Sustainability and Resilience, 2024)
Food holds significance beyond mere sustenance for certain communities; it encompasses beliefs, spirituality, and social bonds. The indigenous inhabitants of Cireundeu, a village steeped in tradition, uphold their distinctive culinary culture centered around cassava, a practice deeply intertwined with their beliefs. This study employs a literature review method, employing a bibliometric approach using PoP (Publish or Perish) for article retrieval and VoSviewer for analysis. The bibliometric analysis revealed that the article authored by Jabbaril titled "Resilience of the Cireundeu Indigenous Village Community in Anthropology," published in the Ethnika Budaya Journal, garnered the highest number of citations, totaling 7. The cassava-centric dietary culture is believed to enhance resilience and contribute to environmental conservation, as evidenced by the village's division into three distinct forest zones. The ancestral wisdom of safeguarding nature must be heeded by contemporary society to ensure ecological sustainability.